2003
DOI: 10.1152/ajprenal.00094.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an amiloride binding region in the α-subunit of ENaC

Abstract: .-One of the defining characteristics of the epithelial sodium channel (ENaC) is its block by the diuretic amiloride. This study investigates the role of the extracellular loop of the ␣-subunit of ENaC in amiloride binding and stabilization. Mutations were generated in a region of the extracellular loop, residues 278-283. Deletion of this region, WYRFHY, resulted in a loss of amiloride binding to the channel. Channels formed from wild-type ␣-subunits or ␣-subunits containing point mutations in this region were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
6
24
0
Order By: Relevance
“…Amiloride priming experiments, performed to synchronize hENaC in an open conformation with an occluded pore, revealed that S3969 activation of hENaC was rapid (t1 ⁄ 2 ϳ 5 s) following amiloride removal. The majority of hENaC channels in the oocyte plasma membrane are closed or in a quiescent, nonconducting state (18,19,58), consistent with reports that ENaC exhibits long closed times on the order of seconds (27,59,60 , and % ENaC activation by S3969 (D) in oocytes expressing wild-type ␣␤␥ (WT), ␣␤G37S␥ (␤G37S), ␣R508X␤␥ (␣R508X), or ␤␥ hENaC channels, or no hENaC channels (uninjected) are shown. S3969 strongly activated wild-type ␣␤␥ and ␣␤G37S␥ hENaC, weakly activated ␣R508X␤␥ hENaC, and failed to activate ␤␥ hENaC or uninjected oocytes.…”
Section: Activation Of ␦␤␥ Henac But Not ␣␤␥ Menac By S6969-supporting
confidence: 86%
See 1 more Smart Citation
“…Amiloride priming experiments, performed to synchronize hENaC in an open conformation with an occluded pore, revealed that S3969 activation of hENaC was rapid (t1 ⁄ 2 ϳ 5 s) following amiloride removal. The majority of hENaC channels in the oocyte plasma membrane are closed or in a quiescent, nonconducting state (18,19,58), consistent with reports that ENaC exhibits long closed times on the order of seconds (27,59,60 , and % ENaC activation by S3969 (D) in oocytes expressing wild-type ␣␤␥ (WT), ␣␤G37S␥ (␤G37S), ␣R508X␤␥ (␣R508X), or ␤␥ hENaC channels, or no hENaC channels (uninjected) are shown. S3969 strongly activated wild-type ␣␤␥ and ␣␤G37S␥ hENaC, weakly activated ␣R508X␤␥ hENaC, and failed to activate ␤␥ hENaC or uninjected oocytes.…”
Section: Activation Of ␦␤␥ Henac But Not ␣␤␥ Menac By S6969-supporting
confidence: 86%
“…Amiloride is thought to occlude the pore of ␣ENaC subunits in an open conformation; thus, amiloride functions as an openstate blocker (27) (Fig. 2B, treatment b).…”
Section: Identification Of a Small Moleculementioning
confidence: 99%
“…A six residue tract (WYRFHY) within the ECL of the ␣-subunit was identified as a putative amiloride binding site based on its homology with the antigen binding domain of an anti-amiloride antibody (19,24). Specific mutations within this tract altered the sensitivity of ␣-subunit channels to amiloride, and altered gating characteristics of both ␣ channels as well as ␣␤␥ channels (16,19,20). We and other investigators (16,25) recently reported that Ni 2ϩ is an external inhibitor of ENaC expressed in Xenopus oocytes.…”
Section: Substitutions Of ␥His 239 Within the Extracellular Loop Elimmentioning
confidence: 92%
“…His residues have been found to have key functional roles in enzymes, receptors and ion channels (37)(38)(39)(40). The changes in Na ϩ self-inhibition due to mutations at both His sites raise a question whether they may interact with each other at an ␣-␥ subunit interface and whether this proposed interaction is important for ENaC activity and channel regulation by extracellular factors including metals, amiloride, pH, temperature, and fluid flow (16,19,20,25,(41)(42)(43). In the context of previous studies and our current results, we suggest that a site in the proximity of these His residues has a role in modulating ENaC function.…”
Section: Fig 5 Namentioning
confidence: 99%
“…Theoretically, these Cys residues could form intrasubunit or intersubunit disulfide bonds that normally facilitate proper folding in the endoplasmic reticulum and maintain structural integrity (20). Firsov et al (14) investigated the roles of the ECL Cys residues by a systematic mutation of all 16 Cys residues in the rat ␣ECL, as well as selected mutations of Cys residues in the ␤ECL and ␥ECL. The authors concluded that the Cys-1 and Cys-6 residues of CRD-I in all three subunits and the Cys-11 and Cys-12 of CRD-II in ␣ and ␤ (but not in ␥) ECLs are required for efficient expression of ENaC at the plasma membrane.…”
mentioning
confidence: 99%